2018
DOI: 10.1038/s41395-018-0265-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Prediction of High-Risk Varices in Patients with Primary Biliary Cholangitis and Primary Sclerosing Cholangitis

Abstract: JGA, AB, ET and JG are members of the Baveno Cooperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 28 publications
1
41
1
1
Order By: Relevance
“…This clear and simple definition makes this strategy easy to apply in clinical practice. Thus, our study was able to properly validate the use of the Baveno VI and expanded Baveno VI criteria in Chilean population …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This clear and simple definition makes this strategy easy to apply in clinical practice. Thus, our study was able to properly validate the use of the Baveno VI and expanded Baveno VI criteria in Chilean population …”
Section: Discussionmentioning
confidence: 79%
“…Some studies have replicated the validation of the Baveno VI and expanded Baveno VI criteria in European and Asian patients, observing a similar rate of the sparing of unneeded endoscopies . However, two studies have shown an elevated risk of missing VNT based on Baveno VI consensus (>5%) . Thus, the safety of these criteria must be established in different populations with different epidemiologic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-one studies were retrospective, 27,[30][31][32][35][36][37][38][39][40][41]43,44,47,[50][51][52][53]55,57,58 and hence did not use consecutive or random sampling of patients. All but 2 studies 37,59 did not report explicitly about prior knowledge of LSMs and platelet count by endoscopists.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Importantly, this study evaluated longitudinal trends in TE and found that increasing liver stiffness was independently associated with survival after adjustment for age, sex and bilirubin level . Furthermore, the 2015 Baveno VI guidelines recommending the use of TE and platelet count to rule out clinically significant portal hypertension have been validated in PSC . Therefore, TE is now being considered as a surrogate marker for clinical trials …”
Section: Prognosis and Risk Stratificationmentioning
confidence: 96%